Labour Analgesia - Chandran, Rabindran; Gedam, D Sharad (International Journal of Medical Research and Review, 2017)
Regional anaesthesia is nowadays commonly practised universally. It provides superior pain relief in first & second stages of labour, anesthesia for episiotomy & instrumental delivery.